Efeitos do óleo de cannabis rico em canabidiol sobre a cognição e comportamento de crianças com transtorno do espectro autista: um ensaio clínico - Medeiros, Wandersonia Moreira Brito (2022)
Autism Spectrum Disorder (ASD) is characterized by deficits in the areas of social communication, social interaction, and behavior. The neuropsychological profile of ASD includes recognition of the areas of executive functions, social cognition, and attention. Currently, there are no specific drugs for the treatment of ASD. Drugs are used to help control symptoms associated with the disorder, however with some side effects. Recently, the therapeutic alternatives studied include substances derived from Cannabis, which tend to have fewer harmful side effects. In the present study, the effects of a cannabis oil rich in cannabidiol on the cognitive and behavioral processes of children with ASD were investigated. A randomized, double-blind, placebo-controlled clinical trial was conducted with 60 children aged from 5 to 11 years. The children were divided into two groups: the treatment group, which received the cannabidiol-rich cannabis-based product (CBD); and the control group, which received a placebo product, both using the substance for a period of 12 weeks. Instruments were used to assess ASD symptoms, developmental scales, intelligence tests, attention, executive functions, theory of mind, and face recognition. The results showed that there was no impairment in any of the cognitive functions evaluated in the Cannabis group after using the product. Improvements were observed in measures associated with visual perceptual reasoning, motor coordination, facial expression recognition, and theory of mind after using the extract. In terms of attention, the placebo group showed a better ability to learn the tasks than the experimental group. Minimal side effects have been observed from using the cannabidiol-rich product (sleep disturbance, weight gain and colic). It is concluded that the neuromodulation of phytocannabinoids can take benefits to important cognitive functions in children with ASD, with few adverse effects.